Improving Performance of Laying Hens in Hot Regions by Desert Coolers - Dashe , Y.D.; Raji, M.A.; Abdu, P.A.; Oladele, B.S.; Sugun, M.Y. (International Journal of Poultry Science, 2013)
The efficacy of desert coolers to improve thermal responses and performance of laying hens under heat stress conditions was investigated. Two identical layers houses of deep litter system providing 1600 cm2/hen were used. The first house was equipped with a desert cooler while the other was left without control on air temperature (the control treatment). At 32 week of age, 100 hens from 2 commercial lines (Shaver and Hyline) were housed in each house. The average air temperature in the cooled house was 5.4°C lower (p<0.05) than in the control house. Drinking water temperature in the cooled house was 3.4°C lower (p<0.05) than that in the control house. Rectal temperatures of hens in the cooled house were significantly lower than that of the control. Hens housed in the cooled house showed a significant improvement in feed conversion, significant increase in egg production, egg weight, egg mass, eggshell thickness and eggshell density and significant decrease in unmarketable eggs compared to the control hens. Hyline showed higher (p<0.05) egg production than Shaver when ambient temperature was controlled by the desert cooler. Line had no significant effects on egg weight and egg mass. The net income per hen in the cooled house was US 6.80/hen compared to US 4.20/hen for the controls, which represented a net gain of US 2.60/hen more for the desert cooled hens. Based on these results, the use of desert cooler under hot conditions is efficient and economically feasible.